Service uptake in UCH, Ibandan: a tme flow study (2005)
Objective: To determine the time flow of service uptake as assessed by patients in the eye clinic of UCH with the view of identifying delays in service uptake, the reasons for such delays and ways to improve services. Materials and methods: patients attending the eye clinic of the University College Hospital (UCH) were selected consecutively and interviewed using a semi-structured questionnaire on the amount of time spent waiting for the various services at the eye clinic and reasons for any perceived delays in receiving the services. For under-aged children, their guardians were interviewed. Results: A total of 42 patients we're interviewed, out of which 22 (52.4%) were male. The age range was 5 to 75 years. All the patients were referred, with 78.1 % coming from the general outpatient departrnent of the hospital. They spent between 30 minutes and 2 hours waiting to get their referral letters. Delay was believed to be due to the large number of patients relative to the small number of doctors. Services with extended time flow in the eye clinic include delayed first consultation due to long appointrnent dates (1 to 6 months in 45% of patients studied), need for repeated visits before doctor is seen (2 visits by 78.6% of patients), prolong waiting for nursing procedures (1 to 3 hours by 11 .9%), waiting for doctor's consultation (1 to 3 hours by 21.4%), waiting to pay to the cashier (10 minutes to 1 hour). Reasons for delay include: insufficient number of doctors, few functioning equipment and the poor attitude of some staff. Other services with extended time flow include prolonged surgical bookings of between 1 week and 6 months, mainly due to industrial action by staff, lack of sterile linen due to broken down boiler, unsatisfactory laboratory results, unresolved medical problems or financial constraints. Conclusion: Services in the eye clinic of UCH are perceived by patients to be associated with extended time flow due mostly to the insufficient number of trained staff and functioning equipment, recurrent industrial action and the poor attitude of some staff, which gives rise to patient dissatisfaction and complaints. There is the need to employ more eye doctors to provide functioning equiprnent to re-educate, re-orientate all staff in the eye clinic and in UCH, and in fact, in all public health institutions, to provide a more patient friendly environment through attitudinal change, and to ensure accessible, affordable and acceptable health care.